Illuminating dark matter halo density profiles without subhaloes. Issue 2 (19th September 2020) - Fielder, Catherine E; Mao, Yao-Yuan; Zentner, Andrew R; Newman, Jeffrey A; Wu, Hao-Yi; Wechsler, Risa H
ABSTRACT: Cold dark matter haloes consist of a relatively smooth dark matter component as well as a system of bound subhaloes. It is the prevailing practice to include all mass, including mass in subhaloes, in studies of halo density profiles in simulations. However, often in observational studies satellites are treated as having their own distinct dark matter density profiles in addition to the profile of the host. This difference can make comparisons between theoretical and observed results difficult. In this work, we investigate density profiles of the smooth components of host haloes by excluding mass contained within subhaloes. We find that the density profiles of the smooth halo component (without subhaloes) differ substantially from the conventional halo density profile, declining more rapidly at large radii. We also find that concentrations derived from smooth density profiles exhibit less scatter at fixed mass and a weaker mass dependence than standard concentrations. Both smooth and standard halo profiles can be described by a generalized Einasto profile, an Einasto profile with a modified central slope, with smaller residuals than either a Navarro–Frenk–White or Einasto profile. These results hold for both Milky Way-mass and cluster-mass haloes. This new characterization of smooth halo profiles can be useful for many analyses, such as lensing and dark matter annihilation, in which the smooth and clumpy components of a halo should be accounted for separately.